2019
DOI: 10.1016/s2352-4642(19)30119-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective dorsal rhizotomy in ambulant children with cerebral palsy: an observational cohort study

Abstract: Background Selective dorsal rhizotomy (SDR) is an irreversible surgical procedure involving the division of selected sensory nerve roots, followed by intensive physiotherapy. The aim is to improve function and quality of life in children with cerebral palsy and a Gross Motor Function Classification System (GMFCS) level of II or III (walks with or without assistive devices, respectively). We assessed gross motor function before and after SDR and postoperative quality of life in a study commissioned by NHS Engla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 22 publications
7
38
1
Order By: Relevance
“…These results were comparable to those SDR managed via the traditional way. Not surprisingly, like what earlier studies concluded [1,14,15,[17][18][19], our data showed as well that mild cases improved much better than those severe ones. Cases with their pre-op GMFCS level of II and III had more chance to have their level upgrade than those with IVand V (24/57 vs. 3/24) after the rehabilitation therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were comparable to those SDR managed via the traditional way. Not surprisingly, like what earlier studies concluded [1,14,15,[17][18][19], our data showed as well that mild cases improved much better than those severe ones. Cases with their pre-op GMFCS level of II and III had more chance to have their level upgrade than those with IVand V (24/57 vs. 3/24) after the rehabilitation therapy.…”
Section: Discussionsupporting
confidence: 91%
“…EMG electromyography, SD standard deviation, mA milliampere, ms millisecond Table 3 Changes of muscle tone, muscle strength of the target muscles, and ROM of the joints involved (passive) pre-and postop favorable outcome. Similar results were reported from other centers when SDR was performed in the traditional manner [14][15][16][17]. Further investigation in our study revealed that cases when SDR performed to younger than 6 years old had much Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Although these adolescents hold the promise of achieving India's economic potential, a growing body of work shows persisting challenges to adolescent health and development, including nutrition deficits, exclusion from livelihood choice, social engagement and health services, and unequal gender norms inside and outside the home. [2][3][4][5][6] Adding to this body of work, a new study by Phuong Nguyen and colleagues 7 presents evidence on the health costs of teenage pregnancy in India, which can be lifelong and intergenerational, that affect the lives of a large number of girls.…”
Section: Preventing Teenage Pregnancy In India To End the Cycle Of Unmentioning
confidence: 99%
“…The UK decision was based on a recently published commissioned multicentre prospective open-label trial of SDR that showed the procedure to be associated with significant increases in gross motor function and quality of life for children with moderate cerebral palsy. 1 In Canada, access to SDR for children with this disorder remains variable and limited, with many provinces not performing this procedure and others capping funding or restricting indications. Many Canadian families have travelled south of the border at their own expense and risk to access SDR, which has attracted considerable media attention.…”
mentioning
confidence: 99%
“…Selective dorsal rhizotomy, a surgical procedure to section sensory rootlets in the lumbosacral spine selectively, followed by extensive rehabilitation and physiotherapy, results in improved gait for carefully selected children. 1 Dorsal rhizotomy as a treatment for spasticity has existed for more than 100 years, but the procedure has evolved to be more selective and less invasive. The sensory nerve roots are exposed below the conus medullaris within the cauda equine, separated into rootlets and stimulated; those sensory roots, which generate aberrant motor responses, are cut.…”
mentioning
confidence: 99%